Outcomes and costs analysis of Externalized PyeloUreteral versus internal Double-J ureteral stents after paediatric laparoscopic Anderson-Hynes pyeloplasty. Issue 2 (April 2021) - Paraboschi, Irene; Jannello, Letizia; Mantica, Guglielmo; Roberts, Luke; Olubajo, Seyi; Paul, Anu; Mishra, Pankaj; Taghizadeh, Arash; Garriboli, Massimo
Summary: Background: The gold standard treatment for Uretero-Pelvic Junction Obstruction (UPJO) is laparoscopic dismembered pyeloplasty according to the Anderson-Hynes technique. The internal Double-J ureteral (DJ) and the Externalized PyeloUreteral (EPU) stents are usually the drainage of choice. Only a few articles have compared the clinical impact of the different drainage techniques on the perioperative morbidity and none presented a cost analysis of the incurred hospital stay. Objective: To present the clinical outcome and financial analysis of a cohort of children who underwent a laparoscopic pyeloplasty comparing the use of the DJ versus EPU stent. Study design: Retrospective study of consecutives children who underwent laparoscopic Anderson-Hynes pyeloplasty in a single tertiary paediatric referral centre from January 2017 to March 2020. Patients were grouped according to the type of stent used: DJ stent vs EPU stent. Results: Fifty-three laparoscopic pyeloplasties were performed on 51 patients: 27 (50.9%) had an EPU stent and 26 (49.1%) a DJ stent. There was no statistically significant difference between the two patient groups with regards to surgical time, hospital stay, stent-related complications or the need for re-do surgery. All the EPU stents were removed with an outpatient admission 8.1 days ± 3.1 after surgery while the DJ stents were removed with a cystoscopy 61.6 days ± 30.2 after surgery (p value < 0.001). On a financial analysis (Figure), the hospital costs for stent removal were significantly lower for the EPU stent group (£ 686.7 ± 263.4 vs £ 1425 ± 299.5, p value < 0.01). Discussion: Both drainage methods have some disadvantages. Possible complications associated with DJ stents include migration and artificial vesicoureteral reflux which may lead to higher incidence of Urinary Tract Infections. Possible disadvantages of the EPU stent insertion are related to the damage of the renal parenchyma and to the risk of developing skin site infections and urinary leaks. However, in our series the EPU stent has not been associated with a higher incidence of bleeding, leakage or discomfort. In addition to clinical considerations, there is a financial implication to be considered. With this regard, the EPU stent was associated with a significant reduction in the incurred hospital costs. Conclusions: The use of DJ and EPU stents is equivalent in regards of overall complications and success rates. DJ and EPU stents provided comparable success and complication rates, however the latter avoids the need of an additional general anaesthesia and reduces the overall incurred hospital costs. Summary Figure 1 Comparison of incurred hospital costs (British pounds sterling) between DJ stent and EPU stent for pyeloplasty (A) and stent removal (B). Summary Figure 1